Cytoplasmic Arabidopsis AGO7 accumulates in membrane‐associated siRNA bodies and is required for ta‐siRNA biogenesis - Jouannet, Virginie; Maizel, Alexis (The EMBO journal, 2012)
Formation of trans‐acting small interfering RNAs (ta‐siRNAs) from the TAS3 precursor is triggered by the AGO7/miR390 complex, which primes TAS3 for conversion into double‐stranded RNA by the RNA‐dependent RNA polymerase RDR6 and SGS3. These ta‐siRNAs control several aspects of plant development. The mechanism routing AGO7‐cleaved TAS3 precursor to RDR6/SGS3 and its subcellular organization are unknown. We show that AGO7 accumulates together with SGS3 and RDR6 in cytoplasmic siRNA bodies that are distinct from P‐bodies. siRNA bodies colocalize with a membrane‐associated viral protein and become positive for stress‐granule markers upon stress‐induced translational repression, this suggests that siRNA bodies are membrane‐associated sites of accumulation of mRNA stalled during translation. AGO7 congregates with miR390 and SGS3 in membranes and its targeting to the nucleus prevents its accumulation in siRNA bodies and ta‐siRNA formation. AGO7 is therefore required in the cytoplasm and membranous siRNA bodies for TAS3 processing, revealing a hitherto unknown role for membrane‐associated ribonucleoparticles in ta‐siRNA biogenesis and AGO action in plants.